Ways to Further Expand the Scope of Engagement in Mass Sports - Matkarimova Nargiz Tokhtasinovna , Rashidov Azizbek Ulugbekovich, Ziyadullayev Komil Shamsievich , Ismagulova Gulmira Nuraliyevna (Miasto Przyszłości, 2024)
Based on the study of the characteristics of the market of sports services, to assist in the formation and development of the market of physical education services by determining the main current trends in the development of physical education and sports in the Republic of Uzbekistan, to meet the needs of the population and meet the needs of the population in a balanced way that meets the quality of the high standard of living. its role and place in ensuring the reproduction process was defined.